Do Interventions Targeted at Micro-Entrepreneurs and Small and Medium-Sized Firms Create Jobs? A Systematic Review of the Evidence for Low and Middle Income Countries - Michael Grimm; Anna Luisa Paffhausen (Institute for the Study of Labor (IZA), 2014)
Worldwide 600 million jobs are needed over the next 15 years to keep employment rates at their current level. Governments, non-governmental organizations and donors spend on targeted programs and broader policies to enhance employment creation and the creation of new firms. Because most employment in low and middle income countries is in micro, small and medium-sized enterprises, these firms are especially targeted by such interventions. Despite these efforts, not much is known about which of these interventions are really effective and under which conditions particular interventions work. This systematic review synthesizes the existing evidence on the impact of these programs. Overall the review shows that creating employment is a very complex challenge. Many conditions have to be met before interventions in favor of individual enterprises do not only improve business practices and performance but also lead to additional jobs. A striking finding is that the study design matters for the impacts found; randomized controlled trials find systematically smaller effects than quasi-experimental studies. A significant shortcoming of the literature is that almost nothing is known about long term effects and cost effectiveness.
Keywords: D22; G21; J21; O10; 330; employment; active labor market policy; firm creation; micro; small and medium sized firms; impact evaluations; systematic review